Implementing Link and Match in Practice: A Comparative Study of Management Processes and Graduate Employability Outcomes - Ali Ma'mu Suryana; Abdul Holik (Journal of Innovation and Research in Primary Education, 2026)
Persistent mismatches between vocational graduate competencies and industry requirements have resulted in suboptimal employment absorption rates in Indonesia, particularly amid Fourth Industrial Revolution demands. This study examines link and match management between vocational schools and the business-industrial world (DUDI) to enhance graduate employability. A qualitative comparative case study was conducted at SMK Negeri 2 Cilaku and SMK Negeri 1 Cikalongkulon in Cianjur Regency. Data were collected through semi-structured interviews, participatory observations, and documentation analysis with purposively selected participants including principals, teachers, DUDI representatives, students, and alumni. Analysis employed Miles et al.'s (2014) interactive model based on Robbins and Coulter's (2009) management functions framework. Both schools systematically implemented link and match through comprehensive planning involving early industry participation, integrated organizational structures with frequent communication mechanisms, holistic implementation of eight program pillars including curriculum synchronization and teaching factories, and participatory evaluation processes. Graduate employment absorption reached 68-74% within six months, exceeding national averages. BNSP-certified competency verification significantly accelerated employment timelines. Findings demonstrate that partnership quality—characterized by structural integration, communication intensity, and nationally recognized certification—surpasses partnership quantity in determining employability outcomes. Despite structural constraints including limited regional industry diversity and competency gaps, adaptive institutional responses facilitated program effectiveness, contributing empirical evidence for systematic school-industry collaboration strategies.